2003
DOI: 10.1002/ffj.1264
|View full text |Cite
|
Sign up to set email alerts
|

Constituents of the essential oil of Hemerocallis flava day lily

Abstract: Volatile oil of Hemerocallis flava, the day lily, was obtained by simultaneous distillation-solvent extraction (SDE). Following, the essential oil was analysed by gas chromatography (GC) and gas chromatographymass spectrumetry (GC-MS). Fifty-one components were identified, constituting approximately 92% of the oil. The main constituents of the essential oil were 3-furanmethanol (47.9%) and 2-furancarboxaldehyde (10.4%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 8 publications
(5 reference statements)
0
12
1
Order By: Relevance
“…An unexpected number of volatiles reported by Jiao et al (2016) and Lin et al (2003) in their analysis of 46 genotypes and H. flava, respectively, were not detected in the daylilies in this study. Authentic standards of these compounds were run on the GC-MS because they appeared in previous daylily literature; however, subsequent analysis of their mass spectra and retention times determined they were not present in our study population.…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…An unexpected number of volatiles reported by Jiao et al (2016) and Lin et al (2003) in their analysis of 46 genotypes and H. flava, respectively, were not detected in the daylilies in this study. Authentic standards of these compounds were run on the GC-MS because they appeared in previous daylily literature; however, subsequent analysis of their mass spectra and retention times determined they were not present in our study population.…”
Section: Discussioncontrasting
confidence: 71%
“…At least nine volatiles from this study were reported by Jiao et al (2016), including b-myrcene, (E)-b-ocimene, b-linalool, allo-ocimene, b-caryophyllene, a-farnesene, (E)-nerolidol, phenylethyl alcohol, and indole. Lin et al (2003) also reported phenylethyl alcohol, as well as acetoin, 2-ethyl-1-hexanol, and benzaldehyde. The identification of these compounds in multiple independent studies suggests that these volatiles are indeed part of the fragrance profiles of many daylilies.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Daylily, a type of perennial herbs, is classified in the genus Hemerocallis and the lily Family (Liliaceae). It is primarily native to eastern Asia and widely grown in South China (Lin et al ., ). The flowers of daylily have been widely consumed as cuisine food for thousands of years.…”
Section: Introductionmentioning
confidence: 99%
“…Hemerocallis L. belonging to the family Liliaceae are herbaceous perennials that are used extensively in landscaping and have become one of the four most commonly used garden flowers due to their large, showy flowers and beautiful plant shape (Geng, Gao, He, Gao, & Zhang, 2012;Lin, Cai, Li, Sang, & Su, 2003). The genus Hemerocallis has about 13-15 species, with 11 of these distributed in China (Li & Dong, 2007); therefore, China is the current center of diversity for Hemerocallis.…”
mentioning
confidence: 98%